Managing for Excellence in State Islamic Universities in The 21st Century - Hasbiyallah; Moh Sulhan; Ujang Suyatman (Ta'dib, 2024)
This research aims to identify Managing for Excellence practices at PTKIN in the current era. The research method used is qualitative with a descriptive approach, and data collection techniques include interviews, observation and documentation. The collected data will be analyzed using qualitative analysis techniques, including data collection, data reduction, and data display. Analysis will involve identifying patterns, themes, and trends that emerge from interview data, documentation, and observations. The research results show various types of superior leadership applied at PTKIN Century 21, such as transformational, transactional and participative leadership. In addition, this research reveals best practices in strategic planning, effective organization, implementation of academic and non-academic programs, as well as ongoing evaluation to achieve the excellence of Managing for Excellence at PTKIN. Transformative leadership is leadership that has insight into the future and seeks to improve and develop the organization not for current interests, but for the future. Transformative leadership is always committed to continuous improvement, which is based on a visionary view of the future (better organizational conditions), and encourages staff participation to realize the expected changes. Transactional leadership is a transactional leader determining the desires of followers and providing something that meets those desires in exchange because followers perform certain tasks or find specific goals. Participative leadership is leadership that provides a set of rules to determine the variety and amount of participative decision making in different situations.